Martin Luther Catholic dissident - Stanford, Peter 1961- (Hodder & Stoughton, 2017)
Martin Luther is undeniably one of the makers of the modern world. He risked his life to challenge the corruption and complacency of late-medieval Catholicism, and did it so effectively that his Protestant Reformation broke the stranglehold that the Church of Rome exerted on Europe, redefined the spheres of Church and State and liberated individual believers. From the radical changes we wrought developed ideas of freedom of conscience that thereafter informed every generation up to our own. On the 500th anniversary of Luther nailing his 95 Theses to the door of the Castle Church of Wittenberg, Peter Stanford examines the man, the myth and the mass movement that his act of rebellion provoked. This intimate portrait, drawing extensively on Luther's own remarkable voice, explores this complex, often charismatic man of God and confronts those markers sides to his character that can distance him from contemporary audiences. A cradle Catholic himself, Stanford finds in the current close relationship between Catholicism and Lutheranism- joint hosts of the anniversary celebrations - an encouraging sign for our age: intractable and bloody religious disputes can, with time, be healed. Far from being gloomy, as in his reputation, Martin Luther brings new light; in this and many other ways, he is a man of the moment.